Significance of Product Purchase unaffected by Place of Business - Veronika Nugraheni Sri Lestari; Erdo Nor Yagya; Dwi Cahyono; Nurmawati Nurmawati (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: This study aimed to determine factors influencing consumers’ decision to buy products and prove whether the place of business is an important factor for consumers to decide to buy products. The variables used in this study were 1) price, location and social media, 2) product quality, price, location and social media. Design/methodology/approach: This is a quantitative study with an unknown population. Samples were consumers who incidentally make a purchase at Kober Mie Setan in Surabaya. Sampling technique was coincidence method with a sample of 90 respondents. The data collection technique is a questionnaire with tested validity and reliability. The data analysis technique used to answer the hypothesis is multiple regression. Findings: The results of this study indicate that (1) simultaneous test indicated that the variables of product quality, price, location and social media had a significant effect on consumer purchasing decisions at Kober Mie Setan in Surabaya. This is evidenced by a significance value of 0.000 0.05 and (2) partial test results show that location variable had no positive and significant effect while the product quality, price, and social media variables had a significant effect on consumer purchasing decisions at Kober Mie Setan in Surabaya. This is evidenced by the significance value of 0.383 > 0.05. Product quality variable had a significant effect with a significance value of 0.000 0.05. Price variable had a significant effect with a significance value of 0.002 0.05 and social media has a significant effect with a significance value of 0.014 0.05. Originality/value: This paper is original. Paper type: Research paper